USING GAMES AS A TOOL FOR TEACHING VOCABULARY (Konferensiyalar | Conferences, 2024)
In this article, we investigate how games serve as an effective partner within the journey to grow students' dictionaries and touch off their energy for dialect learning. Thus, lexicon securing could be a foundation of dialect learning, however conventional strategies frequently battle to charm students' consideration and cultivate profound engagement.